Tuning the Refractive Index in Gyroid Photonic Crystals via Lead‐Chalcogenide Nanocrystal Coating. Issue 2 (2nd November 2015) - Goi, Elena; Mashford, Benjamin S.; Cumming, Benjamin P.; Gu, Min
Abstract : The refractive index of a 3D gyroid photonic crystal is engineered via lead‐chalcogenide nanocrystal coating. An alternatively charged layer‐by‐layer deposition protocol is developed to deposit high refractive index PbS thin films on polymer templates fabricated via direct laser writing. Simulation and experiments confirm that the effective refractive index of the photonic crystal is increased by ≈40%.